Understanding the Ageing Process: A Developmental Perspective of the Psychosocial and Spiritual Dimensions - MacKinlay, Elizabeth (Journal of religious gerontology, 2002)
This chapter describes a perspective of psychosocial and spiritual development in the later years of life. It outlines a study of nurses conducted in six nursing homes using pre and post workshop tests to identify changes in nurses' assignment of a list of behaviours as psychosocial or spiritual. Use of SPSS found significant changes between the pre and post tests. Pre workshop tests only identified items as spiritual if they included the word God, or Bible. Results from this study highlight the potential role for nurses in aged care to provide spiritual care as part of holistic care. It also highlights the fact that many nurses feel ill prepared for this role.